Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1021/ac001430a
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Induced Dissociation on a MALDI-Ion Mobility-Orthogonal Time-of-Flight Mass Spectrometer:  Sequencing Peptides from an “In-Solution” Protein Digest

Abstract: Peptide sequencing by surface-induced dissociation (SID) on a MALDI-ion mobility-orthogonal TOF mass spectrometer is demonstrated. SID of approximately 100-fmol amounts of model peptides HLGLAR (m/z 666.8), gramicidin S (m/z 1142.5), and bovine insulin b chain (m/z 3495.5) was accomplished using hydrocarbon-coated gold grids and approximately 20-eV collision energies. The current version of the instrument achieves a mobility resolution of approximately 20 and TOF mass resolution better than 200. Peptide sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 34 publications
1
56
0
Order By: Relevance
“…Russell's group has shown SID to be a simple, yet effective method of activating ions in ion mobility-orthogonal time-of-flight instruments [82][83][84]. The advantage of these instruments is that complex proteomic samples can be separated in the gas phase by ion mobility followed by comparatively faster MS and tandem MS analyses as species exit the mobility drift cell.…”
Section: The Role Of Sid In Developing the Mobile Proton Model And Elmentioning
confidence: 99%
“…Russell's group has shown SID to be a simple, yet effective method of activating ions in ion mobility-orthogonal time-of-flight instruments [82][83][84]. The advantage of these instruments is that complex proteomic samples can be separated in the gas phase by ion mobility followed by comparatively faster MS and tandem MS analyses as species exit the mobility drift cell.…”
Section: The Role Of Sid In Developing the Mobile Proton Model And Elmentioning
confidence: 99%
“…The mass spectrometer was externally calibrated using two-point calibration on C 60 (M r ϭ 720) and C 70 (M r ϭ 840) radical cations (Sigma) [5]. The measurements of collision cross sections were externally calibrated with [M ϩ H] ϩ ions of bradykinin (⍀ meas ϭ 245 Å 2 and substance P (⍀ meas ϭ 292 Å 2 [28]. The 2D IM-MS data were acquired and processed by using custom software (Ionwerks, Inc., Houston, TX, USA).…”
Section: Maldi-im-tofmsmentioning
confidence: 99%
“…For most protein complex ions, we have observed that the signals for a charge state series corresponding to a monodisperse protein assembly display a good correlation (R 2 4 0.99) to a linear relationship between drift time and m/z allowing for polydisperse samples to be identified readily 30 . In addition, plotting data in a format similar to Figure 2b often highlights the presence of post-mobility cell fragmentation 31,32 . If protein complexes are separated by ion mobility as intact assemblies and are activated before mass measurement, any fragmentation products generated will appear at the same drift time as the original parent ion.…”
Section: Introductionmentioning
confidence: 99%